Analisis Kandungan Karbohidrat antara Cholasasia Esculenta dan Ipomoea Batatas (L.) Lamb sebagai Pengganti Karbohidrat pada Diabetes Melitus Gestasional (DMG) - Astik Umiyah (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Introduction : Gestational diabetes mellitus has become a major problem worldwide. Gestational diabetes mellitus affects the health of the mother and fetus directly, this disease is a serious public health problem. Diabetes mellitus can be caused by excessive consumption of carbohydrates. White taro and purple sweet potato are a type of food that has a low glycemic index. This study aims to determine differences in carbohydrate levels in white taro (Cholasasia Esculenta) and purple sweet potato (Ipomoea batatas L) as a substitute for carbohydrates for gestational diabetes mellitus. Methods : His study uses experiments with samples of white taro (Cholasasia Esculenta) and purple sweet potato (Ipomoea batatas L) which are found in the Factory Market in Situbondo Regency. The research variable, namely carbohydrate content, then used a measuring instrument with the luff school method. Analysis of the research data using descriptive data analysis. Results : The research conducted found that the carbohydrate content of purple sweet potato was 0.63 gram/100 gram and that of white taro was 1.035 gram/100 gram. Coclusion Discussion : Purple sweet potato has lower carbohydrate content than white taro, so purple sweet potato is suggested to be an alternative food for people with gestational diabetes mellitus